Moderating role of customer involvement in the relationship between behavioral intention and use behavior - Yuliani, Pande Nyoman; Suprapti, Ni Wayan Sri; K., IGN Jaya Agung Widagda; Piartrini, Putu Saroyini (Edelweiss Applied Science and Technology, 2025)
This study aims to investigate the moderating role of customer involvement in the relationship between behavioral intention and actual usage behavior of digital transaction services. By integrating the Extended Unified Theory of Acceptance and Use of Technology (UTAUT2) with consumer involvement theory, it offers a new perspective on user behavior in the digital banking sector. A quantitative, causal-explanatory research design was applied, targeting long-term users of digital transaction services from two major banks in Bali—one state-owned and one private. Data were collected using structured questionnaires and analyzed using structural equation modeling to evaluate relationships among key UTAUT2 constructs, behavioral intention, actual usage, and the moderating effect of customer involvement. The findings reveal that performance expectancy, social influence, facilitating conditions, price value, and habit significantly influence behavioral intention. Behavioral intention strongly affects actual usage behavior. Importantly, customer involvement significantly moderates this relationship, amplifying the impact of behavioral intention on usage, and also serves as a direct predictor. The study concludes that customer involvement enhances the consistency of digital service use. Practically, the results suggest that banks should personalize digital services, improve communication strategies, and invest in digital infrastructure to boost customer engagement and encourage sustained use of digital banking platforms.